(untitled) - Singh, Jasprit (New York, 2003)
Jasprit Singh presents the underlying physics behind devices that drive today's technologies, utilizing carefully chosen solved examples to convey important concepts. Real-world applications are highlighted throughout the book, stressing the links between physical principles and actual devices
Mô phỏng quang học
Keywords: Semiconductors,Chất bán dẫn; Optical properties,Thuộc tính quang học